Analisis Tindak Tutur Representatif "Cara Belajar Efektif" pada Saluran Youtube Hujan Tanda Tanya - Ariska Novirinda Stefany; Aulia Lathifatul Chalda; Dwi Aulia Putri; Lilis Septiani; Wahyu Wulan Setiyanti; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Hera Septriana (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
The branch of linguistics that studies the external structure of language is pragmatics. Speech acts are analyzed in the field of pragmatics, which is a branch of linguistics that studies language in terms of how language is used (speech). Speech acts are divided into 3 types, namely locution, illocution, and perlocution. This research will examine one of the components of speech acts, namely the illocutionary speech acts of assertive (representative) forms. Representative speech acts are included in the types of speech acts used to explain something, such as facts, statements, affirmations, descriptions, and conclusions. The purpose of this study is to analyze the representative speech acts used in the video "How to Learn Effectively" on the YouTube channel "Hujan Tanda Tanya." There are two types of approaches in this research, namely the descriptive qualitative methodological approach and the pragmatic approach. The methods used in this research are listening, note-taking, and pairing methods. Formal and informal presentation methods are used in this research. There are 7 videos, each of which lasts approximately 6 to 11 minutes, and 140 utterances are found that are included in the representative speech acts. The utterances are divided into 10 types, namely stating, showing, mentioning, informing, suggesting, explaining, giving examples, speculating, reporting, and asking theoretical questions. This research is expected to enrich the literature on pragmatic analysis in the context of digital media, especially related to representative speech acts in educational videos on platforms such as YouTube. In addition, this research is expected to describe and understand various types of speech, especially representative speech.